The Role of Principal Leadership in Improving the Quality of Islamic Elementary School - Haeruman, Andri; Fakhruddin, Fakhruddin; Arbarini, Mintarsih (Educational Management, 2021)
The purpose of this study was to describe and analyze the role of principal leadership in carrying out its function to improve the quality of education at SD Islam Ta’allumul Huda Bumiayu. This research approach is a qualitative approach with a case study design. Data were collected by structured interviews, unstructured interviews, and document studies. The results of this study indicate that the role used by the principal in order to improve the quality of education at SD Islam Ta’allumul Huda Bumiayu is (1) the role of the principal as an educator, where the principal always provides guidance and direction to the board of teachers and students in an educational context. (2) the role of the principal as a supervisor, where the principal always supervises and controls the performance of teachers and school programs. (3) the role of the principal as a leader, where the principal always encourages enthusiasm and confidence of all stakeholders in carrying out their duties. (4) the role of the principal as an innovator, where the principal is always looking for and implementing new ideas and being an example or example for all school members. The benefit of this research is to provide insight into the field of educational management related to principal leadership in improving the quality of education at the primary school level as well as being used as material for evaluating and supporting the work of school principals.